Efforts of a Unit Practice Council to implement practice change utilizing alcohol impregnated port protectors in a burn ICU. Issue 5 (August 2017) - Martino, Amy; Thompson, Leanna; Mitchell, Colleen; Trichel, Rachel; Chappell, William; Miller, Justin; Allen, David; Mann-Salinas, Elizabeth
Highlights: Alcohol impregnated port protectors decreased CLABSI rates in our burn ICU patient population. Bedside nurses can initiate meaningful change and influence patient outcomes. A nurse-led hospital-wide collaborative effort improved patient outcomes by decreasing CLABSI rates. Abstract: Background: Burn patients are an especially high-risk population for development of central line associated bloodstream infections (CLABSI) due to open wounds, extended length of intensive care unit stay, frequent use of central venous catheters, and generally immunocompromised state. Implementing evidence-based practices to prevent these infections is a 2014 National Patient Safety Goal per The Joint Commission. Objectives: The purpose of this project was introduction of a commercially available alcohol impregnated central venous line port protector to reduce the incidence of CLABSI in the burn unit. Methods: The Iowa Model for Implementing Evidenced-Based Practice was used to guide this intervention conducted by the Unit Practice Council. A pre- and post-intervention design compared rates of CLABSI before and after introduction of the port protectors. Results: CLABSI infection rates decreased following the intervention from baseline of 7.3 per 1000 line days to an average of 3.04 per 1000 line days during calendar year 2013. Conclusions: Introduction of an alcohol impregnated central venous line port protector can reduce the incidence of CLABSI in a burn unit.